Access to adolescent sexual and reproductive health services in Accra, Ghana: An exploratory qualitative study - Semira Berhe; Susan Bradley; Ama Fenny; Lydia Aziato; Haddijatou Ceesay; Divya Parmar (Taylor & Francis Group, 2024)
Nearly 31% of the Ghanaian population are adolescents, and these populations persistently face high rates of teenage pregnancies and unsafe abortions. This is despite sexual and reproductive health (SRH) being taught in the school curriculum. In this qualitative study, we explore the factors affecting adolescents' access to, and experiences of, SRH services in Accra, Ghana. We conducted 12 focus group discussions (FGDs) with adolescents and 13 key informant interviews (KIs) in Ghana. The FGDs were conducted with school-going and out-of-school adolescents. KIIs were conducted with various stakeholders working with adolescents or in SRH services. All interviews were conducted in English, audio recorded and transcribed verbatim. We applied the Dahlgren-Whitehead Rainbow model of health determinants and used a thematic analysis. Eight themes were identified, across micro, meso and macro levels, that influence adolescents' SRH access and experience in Accra. These included: family, social networks, the role of schools, health providers and services, the policy landscape, gender norms, cultural norms, and poverty. The findings highlight several factors that influence adolescents' access to appropriate SRH services in this context and demonstrate the need for a multisectoral effort to address structural factors such as harmful gender norms and persistent poverty.